Agriculture and macro-economic reforms in Zimbabwe: a political-economy perspective - Muir-Leresche, Kay (International Food Policy Research Institute, 1998)
Events in Zimbabwe during seven years from the start of economic reforms in 1991 have highlighted the contradictions in the ideologies underlying economic development and institutional reform in the country. They have also highlighted the futility of undertaking partial reforms. Zimbabwe embarked on liberalization of its foreign exchange, banking, marketing and pricing policies in the early 1990s. However, the fiscal deficits continued to increase, and key resource allocation systems remained centrally controlled. The gains from liberalization have been disappointing. The benefits were undermined by high inflation and interest rates caused by excessive government borrowing. High interest rates, together with the rigidities that prevent resources from moving efficiently, make investor response to the liberalized markets very difficult and haphazard. The uncertainty created by conflicting messages portrayed in the rhetoric and actions of the government further reduce investor confidence. This paper traces some of the emerging political and institutional forces that have influenced economic policy and considers the success, constraints and potential for agriculture in Zimbabwe.